Clinical translation of ferumoxytol‐based vessel size imaging (VSI): Feasibility in a phase I oncology clinical trial population - Fredrickson, Jill; Serkova, Natalie J.; Wyatt, Shelby K.; Carano, Richard A.D.; Pirzkall, Andrea; Rhee, Ina; Rosen, Lee S.; Bessudo, Alberto; Weekes, Colin; de Crespigny, Alex (Magnetic resonance in medicine, 2017)
Purpose To assess the feasibility of acquiring vessel size imaging (VSI) metrics using ferumoxytol injections and stock pulse sequences in a multicenter Phase I trial of a novel therapy in patients with advanced metastatic disease. Methods Scans were acquired before, immediately after, and 48 h after injection, at screening and after 2 weeks of treatment. ΔR2, ΔR2*, vessel density (Q), and relative vascular volume fractions (VVF) were estimated in both normal tissue and tumor, and compared with model‐derived theoretical and experimental estimates based on preclinical murine xenograft data. Results R2 and R2* relaxation rates were still significantly elevated in tumors and liver 48 h after ferumoxytol injection; liver values returned to baseline by week 2. Q was relatively insensitive to changes in ΔR2*, indicating lack of dependence on contrast agent concentration. Variability in Q was higher among human tumors compared with xenografts and was mostly driven by ΔR2. Relative VVFs were higher in human tumors compared with xenografts, while values in muscle were similar between species. Conclusion Clinical ferumoxytol‐based VSI is feasible using standard MRI techniques in a multicenter study of patients with lesions outside of the brain. Ferumoxytol accumulation in the liver does not preclude measurement of VSI parameters in liver metastases. Magn Reson Med 77:814–825, 2017. © 2016 International Society for Magnetic Resonance in Medicine